Research on the industry-education integration in higher vocational education from the perspective of social partnership theory - Wei, Yanziye; Ren, Chenxue (Edelweiss Applied Science and Technology, 2025)
As a vital source of skilled and adaptable talent, higher vocational education (HVE) plays a crucial role in supporting industrial development. Amid rapid technological advancement, China faces the urgent challenge of optimizing its vocational education system to meet the evolving needs of emerging industries, equip the workforce with relevant technical skills, and thereby promote economic growth and sustain international competitiveness. Guided by the theory of social partnership, this study investigates the current state of China's higher vocational education and its interplay with industrial development. Drawing on the successful vocational education models of developed countries such as Germany, the United States, and Australia, this research proposes strategic pathways tailored to China's context for deepening industry-education integration. The study offers valuable insights and policy recommendations to enhance the effectiveness of vocational education reform and support the sustainable development of China's industrial economy.